Elucidating the neuropharmacological properties of the novel psychoactive substance and synthetic cathinone, mephedrone - O'Hara, Luke (2022)
Mephedrone (4-methylmethcathinone) is an illicit psychoactive stimulant and synthetic cathinone which gained prominence in the UK as a “legal high” circa 2008, subsequently being made illegal following media reports of adverse effects and links to several fatalities, as well as its structural similarity to amphetamine. Today, mephedrone remains in recreational use worldwide, often consumed alongside traditional illicit substances such as methamphetamine and gamma-hydroxybutyrate (GHB), or legal drugs such as caffeine and alcohol. In rats, co-administration of caffeine with MDMA (3,4-methylenedioxymephampethamine), has been shown to potentiate the elevation of extracellular 5-HT brain levels, a neurochemical correlate of the serotonin syndrome. In humans, this syndrome is characterised by adverse physiological effects including fever, agitation and hypertension.